Technical Training On The Implementation Of Artificial Intelligence Technology To Improve Early Childhood Basic Skills At RA Darussalam 009 - Rr Ayanti Kristantini; Nuraini Purwandari; Devy Puspitasari; Dade Maulana Machdum; Hilman Jihadi; Hanifah Sugiharti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to explore the implementation of artificial intelligence (AI) technology through technical training programs designed to enhance basic skills among early childhood students at RA Darussalam 009. As education enters the era of digital transformation, integrating AI tools in early childhood learning has become increasingly relevant to support cognitive, motor, and language development. The technical training involved both educators and parents to ensure the effective adoption of AI-based applications in daily learning activities. The findings indicate that interactive AI media, when used appropriately, significantly improve early literacy and numeracy skills while fostering student engagement and motivation. This initiative also strengthens the digital competencies of teachers and encourages active parental involvement in children’s learning processes. The research concludes that AI-assisted learning, supported by structured training, holds great potential in advancing the quality of early childhood education.